Analisis Kesalahan Penulisan Gairaigo pada Mahasiswa Tingkat II Tahun Ajaran 2017/2018 Program Studi Pendidikan Bahasa Jepang Universitas Negeri Padang - Yani, Damai (Universitas Muhammadiyah Yogyakarta, 2019)
Gairaigo is one of the learning aspects that must be mastered by Japanese learners. The differences in gairaigo writing from the native language either phonology or morphology make Japanese learners often making mistakes. This papers focused on the form and type of errors in gairaigo writing for students on the second years of the academic 2017/2018 years of the Japanese Language Education study Program at Padang State University. The theory used in this paper was an error analysis method based on the theory of Tarigan (2011). The approach used in this paper was a quantitative and qualitative approach (combination method) with a sequential explanatory model (sequence of proof) proposed by Creswell (2009). Data were taken using test that was open-ended questions and non-test techniques that was interview in accordance with the location of errors in student writing. the form of errors in writing gairaigo of the students at the 2017/2018 on the first indicator was about 76 items with a percentage of 16.89% of phonological errors. On the other hand, the form of morphological errors can be identified as many as 40 items with a percentage of 8.89%. The Gairaigo error in the second indicator was about 26 errors with a percentage of 17.33%. While the error form was about 28 items with a percentage of 18.67%. The type of gairaigo writing errors found in the first indicator was about 131 errors with a percentage of 29.11% for mistake errors. Meanwhile, the lapses errors can be found in 5 errors with a percentage of 1.11%. The type of errors in the second indicator was about 59 errors with a percentage of 39.33%. On the contrary, the type of lapses errors can be found in 2 errors with a percentage of 1.33%.